2012
DOI: 10.3325/cmj.2012.53.612
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C-reactive protein and procalcitonin as predictors of postoperative infectious complications after elective colorectal surgery

Abstract: AimTo assess diagnostic value of perioperative procalcitonin (PCT) levels compared to C-reactive protein (CRP) levels in early detection of infectious complications following colorectal surgery.MethodsThis prospective observational study included 79 patients undergoing elective colorectal surgery. White blood cell count, CRP, and PCT were measured preoperatively and on postoperative days (POD) 1, 2, 3, 5, and patients were followed for postoperative complications. Diagnostic accuracy of CRP and PCT values on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 29 publications
8
36
0
8
Order By: Relevance
“…Similar observations were noted in colorectal surgery [27, 28]. In our study the patient who had signs on the 6 th POD did not have a significantly elevated PCT level on the 1 st and 2 nd POD.…”
Section: Discussionsupporting
confidence: 90%
“…Similar observations were noted in colorectal surgery [27, 28]. In our study the patient who had signs on the 6 th POD did not have a significantly elevated PCT level on the 1 st and 2 nd POD.…”
Section: Discussionsupporting
confidence: 90%
“…These elevated levels after abdominal surgery could be attributed to the transient bacterial translocation from the gastrointestinal tract due to malperfusion of the gut [11]. Oberhofer et al [21] evaluated and compared the roles of perioperative CRP and PCT for the early detection of infective complications after colorectal surgery. They documented that the CRP level on POD 3 and PCT level on POD 2 had similar predictive values for the development of infectious complications, with the best cut-off values of 99.0 mg/L for CRP and 1.34 µg/L for PCT.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off value of PCT on POD 1 in their study was 1.1 ng/ml, with sensitivity of 81% and specificity of 72%. Previous studies reported that PCT is an accurate marker for the early diagnosis of postoperative infective complication [56721] and ventilator-associated pneumonia [8]. On the other hand, some studies concluded that PCT had no added benefit in the prediction of postoperative infection [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of tumour-specific CD4+ T cells by The question is, how to diagnose potentially septic complication early (before clinical symptomatology). Some study showed that C reactive protein and/or procalcitonin are useful biochemical markers that could accurately differentiate between infectious and noninfectious complications (19,20).…”
Section: Grades Definitionmentioning
confidence: 99%